Inability to Extubate Because of Kirshner Wire Transfixation of the Endotracheal Tube - Fukayama, Haruhisa (1987)
A Kirshner wire penetrated and transfixed the endotracheal tube placed to maintain a patient for open reduction of a malar bone fracture. To avoid such incidents, a radiographic check should be made soon after wire placement, and tracheotomy equipment should be available in the oral surgery suite.